Changing the Conversation: Facebook as a Venue for Online Class Discussion in Higher Education - Kent, Mike (MERLOT II, 2013)
In this paper, the author reports on a study of the online activity of students in a final-year unit in the Internet Communications course at Curtin University. Student activity was recorded in the discussion forums of the Blackboard learning management system for three instances of the same unit, in 2011 and 2012. Then, in the latter two of these instances, an additional discussion forum was added, on Facebook, and activity was also recorded. Students’ posts were measured for content, length, and which week of the study period they were posted online. The study found the addition of the Facebook forum resulted in a significantly higher level of student activity, in real terms and across the 13 weeks of the unit. The addition of the Facebook forum did not significantly affect the level of student participation in the Blackboard forum. The use of the Facebook forum also changed the type of interactions by students, with the learners being more involved in discussions about course administration and assignments. Most notably, both students and staff began posting additional links to material that supported learning in the unit, but were not set as part of the unit’s formal readings.